2022
DOI: 10.1002/admi.202101877
|View full text |Cite
|
Sign up to set email alerts
|

Co Nanoparticles Encapsulated in N‐Doped Carbon Nanotubes Grafted CNTs as Electrocatalysts for Enhanced Oxygen Reduction Reaction

Abstract: The exploration of high‐efficiency and inexpensive electrocatalysts for oxygen reduction reaction (ORR) is of critical significance for renewable energy conversion. Herein, an in situ catalytic transformation strategy toward a unique hierarchical nanostructure is reported. In the architecture, Co nanoparticles encapsulated at the tip of bamboo‐like N‐doped carbon nanotubes (NCNTs) are grafted on N‐doped polypyrrole‐derived CNTs. Thanks to the smart design of unique 3D architecture, the NPCN@Co‐NCNTs catalyst d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…31 As described above, the presence of pyridinic-N and graphitic-N species in the carbon support is expected to be highly beneficial for ORR electrocatalysis, lowering the onset potential and increasing the limiting diffusion current density. 20,33 Figure 2e compares the surface N speciation for Co@N−C/N−KB, Co@N−C/ N−KB(NL), and Co/N−KB. The relative N speciation in the three catalysts is presented graphically in Figure 2f.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 As described above, the presence of pyridinic-N and graphitic-N species in the carbon support is expected to be highly beneficial for ORR electrocatalysis, lowering the onset potential and increasing the limiting diffusion current density. 20,33 Figure 2e compares the surface N speciation for Co@N−C/N−KB, Co@N−C/ N−KB(NL), and Co/N−KB. The relative N speciation in the three catalysts is presented graphically in Figure 2f.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, Co-based N–C catalysts for ZABs should be based around cheap and readily available carbonaceous sources. The Co-active materials in Co-based N–C catalysts include metallic Co, oxides, nitrides, chalcogenides, or their composites . Metallic Co nanoparticles offer promise as “Pt-like catalysts” due to their abundant d electrons and good charge transfer ability, which act to enhance ORR kinetics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, an efficient and durable catalyst with a rigid structure, resistant to degradation, is essential for reliable operation. Among metal-free catalysts, defect-rich nitrogen-doped carbon nanotubes (NCNTs) or nanofibers (NCNFs), owing to their robust morphology with modified electronic structure, can offer ORR activity with enhanced durability. Recent investigations have also revealed that the catalytic activity of carbon structures can be enhanced through the encapsulation of metal nanoparticles, leading to the modification of its electronic structure. Thus, the ORR activity of NCNFs can also be increased through the encapsulation of suitable metals such as Fe, Co, etc. However, in all the above cases, the ORR activity of the nonprecious metal-based catalysts has been demonstrated in an alkaline medium with very few reports on the behavior of the catalysts in the acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Oxygen (O 2 ) is the ideal electron acceptor in the cathode of MFCs because of its availability, sustainability, and high redox potential. 7–10 However, the sluggish kinetics of the oxygen reduction reaction (ORR) and a great loss of overpotential, which generally results in 300–400 mV loss 11 and hampers the electron transfer, directly reduce the output power of MFCs and finally limit the application of MFCs as an emerging energy source. 12,13 Therefore, it is highly desirable to search for high-performance catalysts to improve the performance of the cathodes in MFCs.…”
Section: Introductionmentioning
confidence: 99%